A contribution to the Heptageniidae (Insecta, Ephemeroptera) of Thailand and Malaysia - Braasch, Dietrich; Boonsoong, Boonsatien (Zootaxa, 2010)
A brief survey of Heptageniidae (Ephemeroptera) from Thailand and Malaysia is presented. New for science are Afronurus namnaoensis sp. nov., Compsoneuria langensis sp. nov., Epeorus inthanonensis sp. nov., Epeorus (Belovius) khayengensis sp. nov. and Epeorus nguyenbaeorum sp. nov., from Thailand and Compsoneuria perakensis sp. nov. from Malaysia; the new species originate from rivers and streams in the north of Thailand and from some streams in peninsular Malaysia. For the first time, the male of Asionurus primus Braasch & Soldán, 1986 is described and a larva of supposed Iron longitibius Nguyen & Bae, 2004 is illustrated from Thailand. Compsoneuria (Siamoneuria) kovaci Braasch, 2006 was originally not adequately placed in Compsoneuria Eaton, 1881. Its true affiliation remains unclear. Supposed Epeorus hieroglyphicus Braasch & Soldán, 1984, redescribed by Nguyen and Bae (2004), is renamed to Epeorus nguyenbaeorum sp. nov. Two new findings of Heptageniidae are reported from Thailand: Epeorus bifurcatus Braasch & Soldán, 1979 and Iron martinus Braasch & Soldán, 1984. Rhithrogeniella ornata Ulmer, 1939 is recorded from Malaysia for the first time.